Simultaneous poloidal measurements using new magnetically driven reciprocating probes in COMPASS. (March 2016) - Dejarnac, R; Gunn, J P; Dimitrova, M; Hron, M; Panek, R; Pascal, J-Y; Saragosti-Chausy, C; Tamain, P; the COMPASS team,
Abstract: Particles and heat transport in the scrape-off layer (SOL) of tokamaks is not yet fully understood. COMPASS is a small-size tokamakp where the edge plasma is well diagnosed in view of studying the competition between the parallel and the cross-field transport in the SOL. In order to better characterize SOL dynamics, in particular the poloidal asymmetry of the main parameters' radial profiles, two new in-situ magnetically driven reciprocating manipulators have been recently installed in COMPASS. These manipulators, the so-called pecker probes, are two additional poloidal measurement points to the existing two (vertical and horizontal) reciprocating manipulators. The pecker probes are located at the low field side of COMPASS at ±47.5o with respect to the outer mid-plane and are equipped with identical tunnel probe heads, providing simultaneous measurements of the ion saturation current density Jsat, the electron temperature Te and the parallel Mach number M// with high temporal resolution. In this paper, a detailed description of the pecker probe system in COMPASS is described and first measurements are presented.